REFERENTIAL HAEMATOLOGICAL VALUES IN AGOUTIS (DASYPROCTA FULIGINOSA) KEPT IN CAPTIVITY - Andrade E., Dante (2011)
The purpose of the present study was to determine the haematologic values of agoutis (Dasyprocta fuliginosa) bred in captivity at the Patronato Parque Las Leyendas zoo (PATPAL). Twenty three animals were used (11 males and 12 females; 13 juvenile and 10 adults). They were anesthetized with a combination of Ketamine (10 mg/kg BW) and Xilacine (1 mg/kg BW) i.m. The haemathological analysis included haemoglobin (Hb), hematocrit (Ht), count of erythrocytes (RBC) and leucocytes (WBC), mean cell volume (MCV), mean corpuscular haemoglobin (MCH), mean corpuscular haemoglobin concentration (MCHC), and the leukocyte differential. The obtained values were: 6.17 x 106/μl RBC, 5,739 x 103/μl WBC, 40.4% Ht, 12.42 g/dl Hb, 66.56 fl MCV, 20.56 pg MCH, 30.88 g/dl MCHC; and 67.1% neutrophils, 29.6% lymphocytes, 2.39% eosinophils, 0.26% monocytes and 0.56% band neutrophils. The encountered values were similar to those reported in the literature.